2015
DOI: 10.1016/j.tox.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Progression of micronutrient alteration and hepatotoxicity following acute PCB126 exposure

Abstract: Polychlorinated Biphenyls (PCBs) are industrial chemicals that have become a persistent threat to human health due to ongoing exposure. A subset of PCBs, known as dioxin-like PCBs, pose a special threat given their potent hepatic effects. Micronutrients, especially Cu, Zn and Se, homeostatic dysfunction is commonly seen after exposure to dioxin-like PCBs. This study investigates whether micronutrient alteration is the byproduct of the ongoing hepatotoxicity, marked by lipid accumulation, or a concurrent, yet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…4, 27, 40 Hepatic copper was increased in a dose dependent fashion, whereas zinc, selenium, and manganese were decreased (Figure 5). The zinc deficient diet did cause lower hepatic zinc levels whereas zinc supplementation did not increase levels.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…4, 27, 40 Hepatic copper was increased in a dose dependent fashion, whereas zinc, selenium, and manganese were decreased (Figure 5). The zinc deficient diet did cause lower hepatic zinc levels whereas zinc supplementation did not increase levels.…”
Section: Discussionmentioning
confidence: 97%
“…Previous investigations have shown that PCB126 exposure causes decreases in hepatic zinc. 27 In addition, zinc is important in the toxicity of other liver specific agents, like carbon tetrachloride and acetaminophen, since both deficiency and supplementation alter their toxicity. On the basis of these findings, the authors hypothesized that zinc deficiency would exacerbate PCB126 mediated liver injury and supplementation mitigate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hallmark of PCB 126 exposure is liver steatosis in rodent models (Klaren et al, 2015; Lai et al, 2010a; Lai et al, 2011; Lai et al, 2012). For example, histological examinations revealed that acute intraperitoneal exposure to PCB 126 caused a gradual increase in hepatic lipid levels, with lipid levels being significantly higher compared to controls of days 6 and 12 after exposure (Gadupudi et al, 2016; Klaren et al, 2015). These changes were accompanied by diffuse vacuolar changes that are apparent as early as 18 h after PCB 126 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to PCB 126 causes wasting syndrome and alters redox and metal homeostasis in rodent models (Klaren et al, 2015; Lai et al, 2010a; Lai et al, 2011; Lai et al, 2012) by mechanisms involving the AhR (van den Berg et al, 2006). PCB 126 exposure also decreases hepatic glucose levels, followed by a decrease in peroxisomal fatty acid oxidation in male rats (Gadupudi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%